Leadership of School Administrator Affecting Teachers Performance in Schools under the Chanthaburi Primary Educational Service Area Office 2 - ธนูรักษ์, สุรีรัตน์; รักษนคร, กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The sample consisted of 310 school administrators and teachers, determined using the Krejcie and Morgan table. The research instrument was a five-point rating scale questionnaire, with an Index of Item-Objective Congruence (IOC) ranging from 0.67-1 and a reliability coefficient of 0.975. The statistical methods used for data analysis included mean, standard deviation, Pearson’s correlation coefficient, and multiple regression analysis.           The research findings revealed that:• The overall and individual aspects of administrators’ leadership were at the highest level. The highest mean was found in academic leadership, followed by creative leadership, while information technology leadership had the lowest mean.• The overall teachers’ performance was at the highest level. When considering each aspect, performance ranged from high to highest levels. Classroom management showed the highest mean, followed by morality, ethics, and professional code of conduct, while self-development and professional development had the lowest mean.• Administrators’ leadership and teachers’ performance had a very high positive correlation, which was statistically significant at the .01 level (r = 0.931).           4.) Transformational leadership, academic leadership, strategic leadership, and information technology leadership jointly predicted teachers’ performance at a statistically significant level of .05, with a multiple correlation coefficient of 0.936 and a predictive power of 87.60 percent.